INHIBIOTORY EFFECT OF TRYPTOPHAN ON BIOFELIM DEVELOPMENT AND VIABILITY IN METHICILLIN RESISTANT Staphylococcus aureus - Jaafar, Falah Abdul-Razaq Jaafar; Kandala, Nuha J. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This study was aimed to evaluate the antimicrobial and antibiofilm activity of tryptophan against methicillin-resistant S. aureus (MRSA). A 326 samples were obtained from patients attending Al-Karama hospitalcity with various infections including: blood, vagina, acne, nasal cavity, wounds, gums and skin. Only 100 isolates were identified as S. aureus, according to conventional and molecular methods. Detection of mecA and icaAD gene was performed using polymerase chain reaction (PCR) and the results showed 70% of isolates harbored mecA gene (MRSA) and 61% of isolates harbored icaAD gene. The results of detecting quorum sensing (QS) genes, include agr1, agr2, agr3 and agr4, using PCR were revealed, that 27. 14%, 18. 6% and 41. 43 of MRSA isolates were carrying agr1, agr2 and agr3 genes, respectively. The antimicrobial and antibiofilm activity of different concentrations of tryptophan were estimated using colony-forming unit (CFU) assays. The findings revealed that the FSA96 isolate was showed greater ability to resist 2mg/ml of tryptophan in percentage 25. 6% than other isolates (FSW61, FSW69 and FSB76 in percentage (16, 16. 25 and 16. 7) % respectively. The biofilms were showed significantly decrease in their percentages (2.17, 1.64, 3.63 and 1. 49) % at concentration 2 mg/ml of tryptophan for FSW61, FSW69, FSB76 and FSA96 isolates. The present study examined the role of QS (agr1 and agr2) genes in the production of biofilm icaAD gene for three selected MRSA isolates using qPCR. The results indicate the significant influence for the expression of icaAD gene which is associated with the expression of a QS genes (agr1 and agr2) which significantly downregulated after being treated with 2. 0 mg/ml of tryptophan compared with the control that expressed. The results indicate the significant differences for the expression of icaAD gene which is associated with the expression of a QS genes (agr1 and agr2) when showed down regulation after being treated with 2.0 mg/ml of tryptophan compared with the control that expressed.